Evaluation and analysis of virtual tour application acceptance in Cau Belayu Tabanan Village using Technology Acceptance Model (TAM) - Sarja, Ni Ketut Pradani Gayatri; Widana , I Putu Krisna Arta; Sarja, Ni Luh Ayu Kartika Yuniastari (Bulletin of Social Informatics Theory and Application, 2024)
Tourism villages are required to be innovative and creative in promoting their village if it want to survive in the midst of the COVID-19 pandemic situation. Utilise one part of virtual reality, namely virtual tours, can be used to promoting tourism villages, one of them is the Cau Belayu Tourism Village. Virtual tour is a new technology, therefore it is necessary to analyze the virtual tour that was developed with the aim of measuring the level of usefulness and level of user acceptance of the Virtual Tour of Cau Belayu Tourism Village. The purpose of this research is to evaluate and analyze the level of user acceptance of the Cau Belayu Tourism Village Virtual Tour so that in its implementation it can attract tourists to visit the village and increase the tendency of tourists to visit tourist villages directly. This research uses the Acceptance Model (TAM) evaluation model which has been proven to be effective in evaluating the level of acceptance of other technologies, therefore it is also used to evaluate the developed virtual tour. Several constructs used as test variables from the TAM model are used, namely Perceived Ease of Use (PEOU), Perceived Enjoyment (ENJ), Perceived Usefulness (PU), and Tendency to visit Actual Sites (TenAS). The results of hypothesis testing show that the four hypotheses are proven, namely H1: PEOU has a positive effect on PU with a significance value of 0.0030 < 0.05, H2: PEOU has a positive effect on ENJ with a significance value of 0.0030 < 0.05, H3: PU increased TenAs with a significance value of 0.007 < 0.05 and H4: ENJ increased TenAs with a significance value of 0.00 < 0.05.